Issues of Implementing the Resocializing Function of Probation Control in the Republic of Kazakhstan - ALIBEKOVA, Aida Batyrbekovna (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The article considers the issues of estimating the place of the probation institution in Kazakhstan legal and law-enforcement reality. Today, the modernization processes of Kazakhstan criminal policy, where the sphere of punishments, not related to deprivation of liberty and widely used in international practice, shall be subject to deeper modernization, are being actively discussed socially and in academic community. In this regard, a great number of questions to the newly established probation institution in the Republic of Kazakhstan, especially related to its future efficiency, arise. The objective set by the author of this article provides for the analysis of international and domestic law regulating probation control, as well as the prospects for its further improvement in the Republic of Kazakhstan. The article reviews opinions of domestic and foreign scientists carrying out research into the probation institution and its modifications, as well as into its application experience in foreign countries. The position, based on which the existing legal instruments, provided they are duly modified, can be used for efficient implementation of the probation function in the Republic of Kazakhstan, is substantiated. Based on the analysis of various regulatory prescriptions, doctrine approaches to the issue, expert surveys, and the prospects for the expanding of the object composition of persons under supervision, the conclusion about the necessity of establishing a probation service as an independent body, and expanding its function and specialization, has been made.